Mapping the location of psoralen crosslinks on RNA by mung bean nuclease sensitivity of RNA.DNA hybrids. - Hui, C F (1985)
An indirect high resolution method has been developed for finding the location of intrastrand crosslinks in RNA. An end-labeled DNA strand that overlaps the approximate crosslink position is hybridized to the RNA and then treated with mung bean nuclease. The resulting digest is analyzed on a sequencing-type gel. The method was tested with the major psoralen crosslink seen in the 16S rRNA of inactivated Escherichia coli 30S ribosomal subunits. This crosslink was previously mapped between residues 930 +/- 25 and a region close to the 3' end by electron microscopy. The new indirect method reveals that the crosslink occurs between residues 919 and 923 and residues 1530 and 1534. When these results are examined in the light of existing consensus secondary structure models for the 16S rRNA, it appears that the Shine-Dalgarno sequence is located close to the peptidyl tRNA binding site.